Environnement et inégalités sociales - Cornut, Pierre; Bauler, tom; Zaccaï, Edwin (Architecture, aménagement du territoire, environnement, 2007)
Since its inception, environmental protection has been based on the natural sciences and technology and, more recently, has interacted with the economy, but its relations with social aspects have been the subject of less attention. 'Warning. The environment, however, calls for the preservation of (quality of) life, and man is a social animal. However, if the objective of environmental protection is generally formulated in a consensual way, it will obviously be declined in different ways according to social differentiations. Taking full account of these interactions leads to formulating a series of questions. How are environmental impacts distributed in a society? How can objectives and actions oriented towards the protection of the environment be read in the prism of the social categories? What are the beneficiaries and the losers in particular? Who can make their voices heard and influence the criteria? What avenues to consider for limiting the negative impacts of economic growth with a dual objective of social equity and the reduction of environmental nuisances? These questions question fundamental aspects of sustainable development and political ecology. They are studied in this book, in theory and in many practical cases locally and nationally, but also more widely in the world.